Sémantique synchronique : synonymie, homonymie, polysémie - Schogt, Henry G. (University of Toronto Press, 2018)
The three well-known phenomena of synonymy, homonymy and polisemia serve as a starting point for this study which serves to clarify the problem of signification and linguistics. This attempt to clarify the problem of meaning in linguistics takes as its starting point the well-known phenomena of synonymy, homonymy, and polysemy.